Circus in the Prater - Unknown:::Creator::::::::::::; Friederich, Johann Konrad, 1789-1858.:::Contributor:::::::::::: (Frankfurt am Main; Comptoir für Literatur und Kunst; Germany)
Engraving of the Prater in Vienna